Participation, representation and representativeness in the decision-making process of River Basin Committees:: concepts, reflections and discussions - Barbosa, Flavia Darre; Hanai, Frederico Yuri; Romera e Silva, Paulo Augusto (Sustainability in Debate, 2016)
This study reflects about (i) the effectiveness of the participation of members of river basin committees (ii) representation and representativeness in decision-making process in such committees. These committees, which involve public authorities, civil society and water users encourage participatory management of water resources. However, it is supposed that the effectiveness and the quality of the representation of committee members are compromised by several factors. The research was based on the review of the literature and on the analysis of different situations and possible configurations of social participation. It was found that committees are legitimate instruments for participation and that the quality of representation involves factors related to the performance of their members, such as citizen performance, individual awareness of collective spaces and interest sharing.